Effect of L-carnitine on potassium dichromate-induced nephrotoxicity in rats: modulation of PI3K/AKT signaling pathway - Abeer A A. Salama; Rasha E Mostafa; Rania Elgohary (Wolters Kluwer Medknow Publications, 2022)
Background and purpose: Kidney diseases impose significant global health challenges. Potassium dichromate (PD) is a heavy metal frequently associated with nephrotoxicity. PD prompts oxidative and inflammatory injuries in renal tissues. L-carnitine is a naturally-occurring amino acid commonly used as a supplement. Experimental approach: Forty rats were randomly allocated into 5 groups. Group 1 (normal) received only saline. Nephrotoxicity was induced in the remaining groups by PD (15 mg/kg; i.p). Group 2 served as a nephrotoxic group. Groups 3-5 received L-carnitine (25, 50, and 100 mg/kg; p.o.), respectively for 4 weeks. Findings/Results: PD administration resulted in elevated serum creatinine and blood urea nitrogen accompanied by diminished reduced glutathione and elevated malondialdehyde, tumor necrosis factor-alpha, and transforming growth factor-beta renal tissue contents relative to normal rats. PD also produced apoptotic histopathological injuries and down-regulated PI3K/Akt signaling pathway; signifying ongoing apoptosis. In the current work, L-carnitine use in the selected dose levels resulted in improvement of all the aforementioned serum, renal tissue, and histological parameters relative to nephrotoxic rats. L-carnitine up-regulated PI3K/Akt signaling pathway that was down-regulated post PD use. Conclusion and implications: Collectively, the study highlighted that the possible mechanisms beyond the beneficial effects of L-carnitine are mainly through its antioxidant as well as anti-inflammatory actions. L- carnitine significantly abrogated apoptosis via up-regulation of PI3K/Akt signaling pathway and signified restoration of normal renal cell proliferation and functionality.